2020
DOI: 10.3390/min10040361
|View full text |Cite
|
Sign up to set email alerts
|

Native Seedling Colonization on Stockpiled Mine Soils Is Constrained by Site Conditions and Competition with Exotic Species

Abstract: Sites disturbed through mining practices can be challenging to restore with native vegetation, as the path of ecological succession is often unknown and hard to predict. We conducted an establishment study that explored restoration strategies to increase native vegetation on a newly formed stockpile of soil at New Gold’s New Afton Mine in British Columbia, Canada. Establishment of native species in semi-arid grasslands is often constrained by seed and seedling microsite limitations, so treatments were imposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Reclamation methods for revegetation of degraded land should find a balance between the short‐term needs like soil stabilization and erosion control and long‐term objectives, such as increasing native biodiversity or establishing woody vegetation. Site preparation and seeding may assist in reducing the negative environmental conditions that often constrain establishment, like poor soil quality, limitations in the number of microclimates suitable for growth and establishment of different species, and propagule pressure by exotic species (Zobel et al, 2000; Martin and Wilsey, 2006; Baethke et al, 2020). Unfortunately, we were unable to assess plant‐functional groups or exotic species, but the relatively rapid cover provided by seeding may aid in reducing the probability of establishment of invasive plants (Jessop and Anderson, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reclamation methods for revegetation of degraded land should find a balance between the short‐term needs like soil stabilization and erosion control and long‐term objectives, such as increasing native biodiversity or establishing woody vegetation. Site preparation and seeding may assist in reducing the negative environmental conditions that often constrain establishment, like poor soil quality, limitations in the number of microclimates suitable for growth and establishment of different species, and propagule pressure by exotic species (Zobel et al, 2000; Martin and Wilsey, 2006; Baethke et al, 2020). Unfortunately, we were unable to assess plant‐functional groups or exotic species, but the relatively rapid cover provided by seeding may aid in reducing the probability of establishment of invasive plants (Jessop and Anderson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The increased cover on seeded sites to which biosolids have been applied may be a result of increased nitrogen and phosphorus availability (Meyer et al, 2002; You et al, 2017). Agronomic species are often used to revegetate severely disturbed sites, which are able to take rapid advantage of increases in nutrient availability and provide rapid cover (Carrick and Krüger, 2007; Bochet et al, 2010; Baethke et al, 2020). Research remains limited on the use of native seed mixes when reclaiming severely degraded lands (Alday et al, 2011; Baethke et al, 2020), but it will be important to select plant species that are able to compete in this nutrient‐rich environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that non‐native/naturalized grasses benefit more from nutrient addition show that this is still a challenge to overcome (Huang et al, 2018). Restoring with native seedlings may be an alternative and contribute to increase native species’ success (Baethke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since bringing back mining sites to a state close to the historical ecosystem can be challenging, restoration efforts often lead to the creation of a novel ecosystem with different species, interactions, and functions than the original site (Hobbs et al, 2009). Novel ecosystems can be valuable natural assets, but there is an increasing desire to re‐establish near‐natural ecosystems to sustain biodiversity and improve resilience in a changing climate (Baethke et al, 2020; Salgueiro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the geo-ecological regeneration of disturbed areas, a systematic approach to revegetate the area with native vegetation to foster positive natural ecological processes is an attractive approach. Baethke et al reported efforts conducted in semi-arid grasslands in British Columbia, Canada [13]. They found that native seedling establishment is primarily seed-limited, and that proper raking and tilling help keep incursion of exotic species at bay.…”
mentioning
confidence: 99%